The Potential Role of Appetite in Mediating the Relationship of Whole Grains and Body Weight. Issue 5 (September 2021) - Sanders, Lisa M.; Maki, Kevin C.
Abstract : Observational studies have consistently shown a relationship between whole grain (WG) intake and lower body weight and body weight gain over time. However, randomized controlled trials (RCTs) have not established a consistent causal relationship between WG intake and body weight. There are several plausible mechanisms for how WGs may be able to influence body weight, particularly through effects on appetite and energy intake. Recently, several systematic reviews and meta-analyses have evaluated WG intake and the relationship to body weight in observational studies and RCTs, as well as relationships to appetite and energy intake in RCTs. This review summarizes these recent findings and explores how modest changes in short-term appetite may impact energy intake and body weight in the long term. In addition, reasons for possible inconsistencies in RCTs and observational studies on body weight will be discussed, as well as the limitations of the current research and future opportunities to improve the relevance of the research for public health.